2012
DOI: 10.5923/j.plant.20120201.06
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Growth of Seedlings of Two Rhododendron Tree Species along an Altitudinal Gradient in a Temperate Broad Leaved Forest of Arunachal Pradesh, India

Abstract: Seedling survival and growth of two Rhododendron species viz., Rhododendron kenderickii and Rhododendron grandewere studied along an altitudinal gradient in a temperate forest. Differences in survivality and relative growth responses of the two selected rhododendrons in terms of height, collar diameter and leaf number were monitored seasonally. High seedling mortality was recorded highest in winter season as well as in the higher altitude. Both the species attain maximum growth in terms of height, collar diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The result depicted Asteraceae family as the most dominant in Pinus wallichiana understory vegetation followed by Rosaceae and Lamiaceae. Rahman et al [24] had also reported same trends of family dominance in their studies whereas, Behera et al [25], Paul (2008), and Bharali et al [26] reported similar trends of family dominance (Asteraceae, Ericacaea and Rosaceae). The species diversity under monotype forest is possibly due to altitude, topographic and physiographic conditions.…”
Section: Discussionmentioning
confidence: 70%
“…The result depicted Asteraceae family as the most dominant in Pinus wallichiana understory vegetation followed by Rosaceae and Lamiaceae. Rahman et al [24] had also reported same trends of family dominance in their studies whereas, Behera et al [25], Paul (2008), and Bharali et al [26] reported similar trends of family dominance (Asteraceae, Ericacaea and Rosaceae). The species diversity under monotype forest is possibly due to altitude, topographic and physiographic conditions.…”
Section: Discussionmentioning
confidence: 70%
“…From June, with the onset of monsoon and increase in soil moisture content, survival rate of the seedlings was stabilized. Increase in survival rate of seedlings during the wet season is reported by various researchers (Tompsett 1986, Lieberman & Li 1992, Bharali et al 2012. Lower mortality rate recorded in the second year observation than the first year observation may be attributed due the establishment of the seedling towards the preliminary stage of sapling.…”
Section: Phenological Observationsmentioning
confidence: 74%
“…These studies have suggested gap dynamics as an alternative management technique for the degraded and over-logged Dipterocarp forests. Studies on species-specific seedling growth and survival in northeast India is sparse with only a few documentations (Bharali et al 2012, Saikia & Khan 2012a, Saikia & Khan 2012b). …”
Section: Wwwtropicalplantresearchcommentioning
confidence: 99%
“…According to Khumbongmayum et al (2005), the gradual acceleration in seedling growth rates during the rainy season may be caused by both the increased moisture content of the soil and the quick decomposition of litter. ANOVA results showed a non-significant effect of season on seedling growth (Table 4), however, Bharali et al (2012) reported positive effect of different seasons of the year on seedling growth in two Rhododendron species of Arunanchal Pradesh. determined by the ability of species to adapt their morphology and physiology to their environment (Rose, 2000).…”
Section: Seedling Survival and Mortalitymentioning
confidence: 95%